Hate speech review in the context of online social networks - Chetty, Naganna; Alathur, Sreejith (Aggression and violent behavior, 2018)
Advances in Internet Technologies (ITs) and online social networks have made more benefits to humanity. At the same time, the dark side of this growth/benefit has led to increased hate speech and terrorism as most common and powerful threats globally. Hate speech is an offensive kind of communication mechanism that expresses an ideology of hate using stereotypes. Hate speech targets different protected characteristics such as gender, religion, race, and disability. Control of hate speech can be made using different national and international legal frameworks. Any intentional act directed against life or related entities causing a common danger is known as terrorism. There is a common practice of discussing or debating hate speech and terrorism separately. In the recent past, most of the research articles have discussed either hate speech or terrorism. Hate speech is a type of terrorism and follows an incident or trigger event of terrorism. Online social networks are the result of ITs and evolved rapidly through the popularity among youth. As both the activities are near to close and makes use of online social networks, the collective discussion is appropriate. Therefore we have a review on hate speech with different classes and terrorism with cyber use in the framework of online social networks. With the help of combined effort from the government, the Internet Service Providers (ISPs) and online social networks, the proper policies can be framed to counter both hate speech and terrorism efficiently and effectively. •A collective review on hate speech and terrorism in the framework of online social networks•Freedom of expression may be the one of the causes to occur hate speech.•Laws on hate speech are not same in all the countries.•Terrorist attacks lead to generation and propagation of hate speech over the internet.•With terrorist organizations, women are undervalued and considered differently based on the situation.